Description of the larva of Philopotamus achemenus Schmid 1959 (Trichoptera: Philopotamidae) and a larval key for species of Philopotamus in Greece - Karaouzas, Ioannis (Zootaxa, 2014)
The larva of Philopotamus achemenus is described for the first time. The diagnostic features of the species are described and illustrated and some information regarding its ecology and world distribution is included. Furthermore, its morphological characters are compared and contrasted in an identification key for larvae of the Greek species of Philopotamus.